First report of Engytatus varians (Distant, 1884) (Heteroptera: Miridae: Dicyphini) in Eastern Uruguay and preliminary test on its feeding habits - Burla, Juan P.; Carpintero, Diego L.; Castiglioni, Enrique (Entomological Communications, 2021)
The aim of this work is to report the unprecedented presence in Uruguay of Engytatus varians (Distant, 1884), a predator of several pests of Solanaceae, to present its main morphological features and some facts of its biology, and to provide a key for the identification of the Dicyphini species registered in the country. The presence of this predator in our region is of great interest for the development of future research works related to biological pest control and the potential interaction thereof with other predaceous mirids.